2020
DOI: 10.21203/rs.2.16182/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to CKD Care in Rural Communities of India: A Qualitative Study Exploring the Barriers and Potential Facilitators

Abstract: Background Despite the high and rising burden of chronic kidney disease (CKD) in South Asia, factors that influence access to CKD care at the community level have not been studied previously, especially in the rural areas. We conducted a mixed methods study and interviewed key stakeholders to explore the views and experiences of key stakeholders, and identify barriers and potential facilitators that influence access to CKD care at the primary care level in rural India. Methods A total of 21 stakeholders partic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Research conducted in India identified several barriers to access for patients with CKD who needed urgent attention in PHC, recommending the creation of screening programs and specific educational initiatives to improve awareness of this disease. The study also points out that the PHC infrastructure needs to be strengthened for the care of patients with CKD, ensuring trained staff, availability of diagnoses, essential drugs, and creating efficient reference paths for quality care (Jafar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in India identified several barriers to access for patients with CKD who needed urgent attention in PHC, recommending the creation of screening programs and specific educational initiatives to improve awareness of this disease. The study also points out that the PHC infrastructure needs to be strengthened for the care of patients with CKD, ensuring trained staff, availability of diagnoses, essential drugs, and creating efficient reference paths for quality care (Jafar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers at the health system level included shortages of qualified professionals, medicines, fragmented referrals, and care and inadequate follow-up by specialists in hospitals. For patients and health care professionals, access to care in CKD can be improved through educational initiatives to raise awareness about CKD by the health care team in patients and their families by providing supplies and coordinating the care and involving the community health workers providing in-home care (Jafar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mobile applications and e‐health programmes have been successfully initiated for non‐communicable diseases in low‐resource settings 34 . Mobile health technologies in CKD care have also been shown to be acceptable to rural Indians 35 . These strategies can also be implemented when managing children in ESKD. Reducing indirect losses to families Income loss through missed work days can be reduced by increasing the efficiency of clinic visits for ESKD care or living donor evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…4 In LMIC, that remain as resource-constrained settings, there is a need for optimization of the CKD screening strategies which usually challenge the health system. 5 Risk equations or risk scores are a cost-effective alternative for CKD screening. 6 These equations are less invasive and accepted by the general population; 7 also, they require less resources like laboratory tests.…”
Section: Introductionmentioning
confidence: 99%